Protection of Antarctic microbial communities – ‘out of sight, out of mind’ - Hughes, Kevin A.; Cowan, Don A.; Wilmotte, Annick (Frontiers in Microbiology, 2015)
Recent advances in molecular biology techniques have shown the presence of diverse microbial communities and endemic species in Antarctica. Endemic microbes may be a potential source of novel biotechnologically important compounds, including, for example, new antibiotics. Thus, the scientific and biotechnological value of Antarctic terrestrial microbial habitats can be compromised by human visitation to a greater extent than previously realized. The ever-increasing human footprint in Antarctica makes consideration of this topic more pressing, as the number of locations known to be pristine habitats, where increasingly sophisticated cutting-edge research techniques may be used to their full potential, declines. Examination of the Protected Areas system of the Antarctic Treaty shows that microbial habitats are generally poorly protected. No other continent on Earth is dominated to the same degree by microbial species, and real opportunities exist to develop new ways of conceptualising and implementing conservation of microbial biogeography on a continental scale. Here we highlight potential threats both to the conservation of terrestrial microbial ecosystems, and to future scientific research requiring their study.